Aprotinin reduces the procalcitonin rise associated with complex cardiac surgery and cardiopulmonary bypass - Maruna, Pavel; Klein, A. A; Kunstýř, Jan; Plocová, Kateřina M; Mlejnský, František; Lindner, Jaroslav (Physiological research, 2013)
Aprotinin, a nonspecific serine protease inhibitor, has been primarily used as a haemostatic drug in cardiac surgery with cardio-pulmonary bypass (CPB). This study investigated the effect of aprotinin on the post-operative levels of procalcitonin (PCT) and a set of cytokines in patients undergoing pulmonary artery endarterectomy (PEA). We analyzed 60 patients with chronic thromboembolic pulmonary hypertension undergoing PEA. 30 patients (Group A) were treated with aprotinin (2,00,00 IU prior anesthesia, then 2,00,00 IU in CPB prime and 50,00 IU per hour continuously); a further 30 patients (Group B) received tranexamic Acid (1 g before anesthesia, 1 g after full heparin dose and 2 g in CPB prime). PCT, TNFalpha, IL-1beta, IL-6, and IL-8 arterial concentrations were measured from before until 72 hours after surgery. Aprotinin significantly affected early post-PEA plasma PCT. Patients treated with aprotinin (Group A) had lower peak PCT levels compared to patients in Group B (1.52 ng/ml versus 2.18, p=0.024). Postoperative peak values of PCT and IL-6 correlated closely in both groups (r=0.78, r=0.83 respectively). Aprotinin attenuates the post-PEA increase of PCT in the same manner as other pro-inflammatory cytokines. Significant correlation between PCT and IL-6 post-surgery may be indicative of an indirect IL-6-mediated pathway of PCT alteration.
Keywords: Protein Precursors; Tranexamic Acid; Female; biologické markery; Hypertension, Pulmonary; aprotinin; Cardiac Surgical Procedures; Biomarkers; hemostatika; Aprotinin; Interleukin-8; výsledek terapie; ženské pohlaví; Calcitonin; Tumor Necrosis Factor-alpha; Up-Regulation; Time Factors; časové faktory; kardiopulmonální bypass; lidé; Inflammation Mediators; kardiochirurgické výkony; Endarterectomy; upregulace; Interleukin-6; Treatment Outcome; proteinové prekurzory; Cardiopulmonary Bypass; Pulmonary Embolism; interleukin-8; kyselina tranexamová; TNF-alfa; Interleukin-1beta; plicní embolie; Male; Aged; interleukin-6; endarterektomie; plicní hypertenze; interleukin-1beta; mediátory zánětu; lidé středního věku; kalcitonin; senioři; mužské pohlaví; Middle Aged; Hemostatics; Humans